UNMET MEDICAL NEEDS IN HIGH-RISK CARDIOVASCULAR PATIENTS WITH FAMILIAL HYPERCHOLESTEROLEMIA - Svetoslav Tsenov; Evgeni Grigorov; Valentina Belcheva (Peytchinski Publishing, 2021)
Cardiovascular (CV) diseases are a major burden for all the healthcare systems around the world. Public health and medical advances continue to beneficially affect CV patients health. In the last decades, many new medicinal products for hearth problems were discovered and received a marketing authorization. Elevated low-density lipoprotein cholesterol (LDL-C) levels have been linked to major CV risk. The objective of this study was to review the medical needs in high-risk cardiovascular patients with familial hypercholesterolemia undergoing pharmacological treatment with statins and the degree of attained lipid control. A conclusion it can be stated, that there is a significant unmet medical need for a potentially effective treatment, which can supplement the statin therapy, enabling vulnerable populations to achieve sufficient control of LDL-C, and thus provide an alternative for patients with statin intolerance or where this group of medicinal products are not clinically appropriate.